Manajemen Keuangan pada Badan Usaha Lembang Tallu Lolona - Marinus Ronal; Lisa Kurniasari Wibisono; Mey Enggane Limbongan; Astriwati Biringkanae; Isak Pasulu; Elisabet Pali (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2025)
Badan Usaha Lembang (BumLem) Tallu Lolona faces challenges in financial management that affect the sustainability of its operations, which include credit provision and rice and coffee milling services. This study aims to enhance the capacity of its administrators and managers in financial management through mentoring and training. The methods employed include classical training, practical workshops, and group discussions. The results indicate that participants successfully grasped the basic principles of financial management, improved their ability to prepare financial reports, and identified solutions to financial issues through discussions. It is expected that this initiative will create new institutions, foster positive behavioral changes, and cultivate local leadership in BumLem’s financial management.